An Assessment of Municipal Solid Waste Plans, Collection, Recycling and Disposal of Metro Manila - World Bank (Washington, DC, 2022)
This study performed an assessment of the solid waste management (SWM) plans and the collection, recycling, and disposal conditions of the 17 Local Government Units (LGUs) of Metro Manila to determine the gaps and barriers hindering the effective implementation of Republic Act 9003 (RA 9003), particularly the recovery and recycling of plastic waste. The results were used to identify potential investment opportunities that could contribute to improved plastic waste management and the overall SWM systems of LGUs. The assessment focused on the approved 10-Year SWM plans, online reports of the National Solid Waste Management Commission (NSWMC), data provided by the Metro Manila Development Authority, interviews with the heads and staff of the SWM functional groups of each LGU and related government institutions, and a web search on government and private sector initiatives on recycling and plastic waste management. Metro Manila is composed of 16 cities and 1 municipality, with a combined total 1,712 barangays. Its land area of 619.1 square kilometers is bounded by large bodies of water on the west (Manila Bay) and east (Laguna de Bay). The central section LGUs are traversed by the main channel of the Marikina-Pasig River and the rest are drained by the tributaries. These waterways and waterbodies are plagued by illegally disposed and uncollected waste. The condition is exacerbated during floods when additional uncollected waste and litter move down the gradient and clog man-made canals and natural waterways. Eventually, the waste is discharged into Manila Bay or deposited into the 50 existing pumping stations of Manila. The institutional, legal, and financial aspects as well as the management of hazardous waste were not covered in this assessment. The assessment did not consider the effects of the pandemic on waste generation. Due to the restrictions brought on by the pandemic, field verification of the data gathered through interviews was not conducted.